NTR1 is required for transcription elongation checkpoints at alternative exons in Arabidopsis - Dolata, Jakub (EMBO J, 2015)
The interconnection between transcription and splicing is a subject of intense study. We report that Arabidopsis homologue of spliceosome disassembly factor NTR1 is required for correct expression and splicing of DOG1, a regulator of seed dormancy. Global splicing analysis in atntr1 mutants revealed a bias for downstream 5′ and 3′ splice site selection and an enhanced rate of exon skipping. A local reduction in PolII occupancy at misspliced exons and introns in atntr1 mutants suggests that directionality in splice site selection is a manifestation of fast PolII elongation kinetics. In agreement with this model, we found AtNTR1 to bind target genes and co-localise with PolII. A minigene analysis further confirmed that strong alternative splice sites constitute an AtNTR1-dependent transcriptional roadblock. Plants deficient in PolII endonucleolytic cleavage showed opposite effects for splice site choice and PolII occupancy compared to atntr1 mutants, and inhibition of PolII elongation or endonucleolytic cleavage in atntr1 mutant resulted in partial reversal of splicing defects. We propose that AtNTR1 is part of a transcription elongation checkpoint at alternative exons in Arabidopsis.